Socialization of UMKM Merchandise Inventory Management During the Covid 19 Pandemic in Desa Suka Makmur - Harkim Simamora; Rejekia Vaizal Simanungkalit; Maya Andriani; Bambang Sugiharto (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2021)
The Covid pandemic has had many impacts on people's lives, one of which is the economy. The spread of the virus that requires human activities to be carried out by social distancing (maintaining social distance) and even implementing lockdown measures that have an impact on slowing economic activity (demand and supply). UMKM are one of the sectors affected by this pandemic where there is not only a decline in income, but another impact that is felt by business actors is inventory that accumulates. The implementation of this service activity has provided an understanding to UMKM actors about the importance of inventory management for UMKMs and increased the participants' ability to manage UMKM finances so that they can survive during this pandemic.